The Use of Zinc Finger Protein Gene to Detect the Presence of Y Chromosome in the Cow - Shamsuddin, Shaharum (1996)
Total genomic DNA from 24 normal cows and a normal male cattle were isolated from leucocyte preparation. Polymerase Chain Reaction (PCR) amplification of these genomic DNA using the PI-5EZ and P2-3EZ primers for ZFX/ZFY gene resulted in a fragment of approximately 440 bp in size from both male and female samples. This PCR product represents part of the ZFX/ZFY gene defined by the primers used. The PCR products were proven to be amplified from bovine genomic DNA from the dot blot hybridization studies. After Pst I digestion, the female samples (ZFX) remained undigested while the male (ZFX/ZFY) showed three fragments of approximately 440 bp, 340 bp and 100 bp. Thus the ZFY gene has a unique Pst I site. The PCR product from a population of 45 female and 47 male cattle was further tested for the presence of the Pst I cleavage. There was no Pst I site in all the female (ZFX) samples, while 45 out of 47 samples from the male were cleaved. From X2 analysis of the data, the Pst I cleavage on ZFY was significantly sex dependent. The restriction analysis of ZFX/ZFY gene showed the existence of a unique Mnl I site on ZFX and more than one Alu I restriction site on both ZFX and ZFY. The PCR product from an infertile female cattle (supposedly, 60, XX and therefore ZFX/ZFX) was subjected to the Pst I digestion, and found to be cleaved indicating the presence of the ZFY gene and possibly the Y chromosome. The latter was confirmed by cytogenetic analysis. Post mortem and autopsy evaluation of the animal showed a partial development of male characteristic and a defective female reproduction system The use of the peR diagnosis for the presence of the Y chromosome was applied to a population of 30 suspected infertile female animals, and two were found to have the ZFY gene indicating the possible presence of the Y chromosome. Thus, peR amplification of the ZFX/ZFY gene followed by Pst I digestion and analysis on gel electrophoresis can be used as an approach to establish the presence of the Y chromosome in an infertile female cattle. This approach however, needs to be supported by karyo typing to establish unequivocally the screening procedure.